Education Control Management - Saadah Hayida-o; Alwan Suban (Business Finence Analyst Co.,, 2024)
Educational control management is an important part of the management process that functions to evaluate whether educational performance standards are in line with the goals to be achieved. In addition, it has an important role in ensuring the success and achievement of educational goals that have been set. In the quality control stage, it can be done in stages, including planning (plan), implementation (do), inspection (check), and follow-up (action). There are also several elements in the control process such assensors (detectors), assessors, effectors, and communication networks. A deep understanding of educational control management can support the principal in carrying out his/her responsibilities to achieve the set targets, thereby being able to create an efficient and standardized education system